2012
DOI: 10.1590/s1413-35552012005000020
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of active and passive forces of the pelvic floor muscles in women with and without stress urinary incontinence

Abstract: Background: The reduction of the pelvic floor muscles (PFM) strength is a major cause of stress urinary incontinence (SUI). Objective:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 31 publications
(43 reference statements)
1
28
0
5
Order By: Relevance
“…No further topic related articles were found by searching the reference lists of the included (systematic) reviews. Fourteen studies were finally included in this systematic review and were divided into two study types: (a) nine studies comparing SUI with healthy controls (non‐randomized cross‐sectional, observational, explorative clinical studies with control) and (b) five studies concerned clinical trials or intervention studies (non‐controlled pre‐post design) with females suffering from SUI. Two papers out of the cross‐sectional studies were published based on the same data investigating the physics of a custom‐built vaginal probe and considering the clinical interpretation of the gathered data respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No further topic related articles were found by searching the reference lists of the included (systematic) reviews. Fourteen studies were finally included in this systematic review and were divided into two study types: (a) nine studies comparing SUI with healthy controls (non‐randomized cross‐sectional, observational, explorative clinical studies with control) and (b) five studies concerned clinical trials or intervention studies (non‐controlled pre‐post design) with females suffering from SUI. Two papers out of the cross‐sectional studies were published based on the same data investigating the physics of a custom‐built vaginal probe and considering the clinical interpretation of the gathered data respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Table shows the major characteristics of the nine studies referring to the cross‐sectional studies. Measurement methods varied among these studies: In six studies strength measurements were performed (used terminology besides strength were force or pressure and measured units Newton or mmH 2 O) while in three studies surface EMG amplitude was assessed. The measurements were performed with various probes, that is, with well‐established medical devices or with custom‐built probes .…”
Section: Resultsmentioning
confidence: 99%
“…Among clinicians, the most typical method for quantification of PF function is digital palpation because it is fast, requires no equipment, and selectively depicts PFM activity better than most available biofeedback devices (Peschers et al 2001b Several manometers van Raalte and Egorov 2015;Ribeiro et al 2016), dynamometers (Dumoulin et al 2004a;Saleme et al 2009;Chamochumbi et al 2012;Romero-Cullerés et al 2017) and EMG techniques Ptaszkowski et al 2015) have been proposed to objectively quantify PF function. However, most of these methods were developed for research purposes, in contrast to the proposed sensor, which is already commercially available and has the advantage of differentiate the effects of maximum contraction of PFMs as opposed to an increase in intra-abdominal pressure (Valsalva) along the vaginal canal (Fig.3).…”
Section: Discussionmentioning
confidence: 99%
“…Two studies did not find differences in tonus between controls and women with urinary incontinence symptoms (Verelst and Leivseth 2004a;Chamochumbi et al 2012) and three others reported lower tonus in the incontinent group (Morin et al 2004a;. Similarly, one study did not find differences in the PFM maximum force between groups (Morin et al 2004a), while four others reported lower force in the incontinent group (Verelst and Leivseth 2004a;Chamochumbi et al 2012). These conflicting findings could be explained by the fact that each study used a different measuring device, for which the force was considered in different portions or orientations of the vaginal canal.…”
Section: Description Of Force Parameters In Women With Pelvic Floor Dmentioning
confidence: 99%
See 1 more Smart Citation